Negative interpretations of ambiguous 'psychosis‐like' and 'anxiety‐like' experiences in recovery from psychosis or anxiety. (13th May 2021) - Sired, Rebecca; Griffith, Emma; Jamalamadaka, Taruna; Salkovskis, Paul
Abstract : Objectives: Fear of relapse (FOR) after experiencing psychosis has been found to predict actual relapse; however, potential mechanisms underlying this relationship have not been investigated. Negative appraisals of 'prodromal symptoms' are believed to play an important role in both psychosis and mental health anxiety (MHA). This study aimed to explore whether people in recovery from psychosis or anxiety disorders show an enduring tendency to negatively interpret ambiguous experiences both related and less related to their previous mental health difficulty relative to controls. Design: Cross‐sectional between‐groups questionnaire design. Methods: Participants self‐reported as in recovery from psychosis ( n  = 33) or anxiety ( n  = 77) or without previous experience of mental health problems ( n  = 61) were recruited online or via NHS services. Interpretations of psychosis‐like, anxiety‐like, and external‐control experiences were measured using the newly developed Experiences Interpretation Questionnaire (EIQ). MHA and FOR were measured using self‐report questionnaires. Results: People in recovery from psychosis interpreted psychosis‐like experiences significantly more negatively than the other groups. Negative interpretations of anxiety‐like experiences were greater than controls but comparable between mental health groups. Contrary to predictions, FOR was not significantly different between the mental health groups. MHA and FOR did not significantly predict negative interpretations of psychosis‐like items in the psychosis group, however, MHA predicted negative interpretations of anxiety‐like items in the anxiety group. The EIQ subscales demonstrated good test–retest reliability. Conclusions: People in self‐defined recovery from psychosis or anxiety are more likely to negatively interpret ambiguous experiences relating to their previous mental health difficulties. Clinical and future research implications are outlined. Practitioner points: People in recovery from psychosis or anxiety appraise possible symptoms of their previous difficulties negatively/catastrophically (as indicating relapse) relative to those without prior MH problems. Clinicians should consider attending to how people in recovery appraise possible symptoms when encouraging early signs monitoring as part of relapse prevention. This may be important to ensure that self‐monitoring leads to helpful responses rather than being counterproductive, with catastrophic interpretations leading to anxiety and thus increasing the risk of relapse. Interventions drawing on CBT principles to address catastrophic interpretations of possible symptoms may potentially be a useful addition to relapse prevention work; in psychosis this may also include symptoms of anxiety.